The effect of wordwall digital game media on improving students' learning outcomes and communication skills in social studies at elementary school - Syarifah Aeni Rahman; Ashar, Ashar; Maria Teresa M. Fajardo (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
This research was conducted to investigate the effectiveness of Wordwall digital games in the context of elementary social studies learning. Specifically, the study sought to: (1) examine the extent to which the use of Wordwall media could enhance students’ academic achievement; and (2) assess the contribution of this interactive platform in fostering students’ communication skills during classroom activities. The study applied a pre-experimental approach using a one-group pretest–posttest design. In this design, a single class was observed without the inclusion of a control group. The participants consisted of 25 fourth-grade students enrolled at SDN Bontoranum II in Makassar. Data were gathered through the administration of tests, direct classroom observations, and the distribution of questionnaires. The collected information was subsequently analyzed using both descriptive and inferential statistical techniques. The results demonstrated a clear improvement in student performance following the integration of Wordwall digital games into the learning process. This progress was reflected in the students’ quiz scores and the comparative analysis between pretest and posttest results. Before the use of Wordwall, the average pretest score in social studies was 68, which fell into the low category. After the intervention, the mean posttest score rose significantly to 88.0, categorized as high. Further statistical analysis through a t-test confirmed that the improvement was significant. The significance value obtained (Sig = 0.013) was smaller than the predetermined alpha level of 0.05, indicating that the use of Wordwall digital games had a meaningful impact on student learning outcomes in social studies. In addition to cognitive gains, the study also highlighted improvements in students’ communication skills. The integration of Wordwall games encouraged greater classroom engagement, evidenced by students’ active participation, enthusiasm in discussions, and increased confidence in expressing opinions during lessons. These findings suggest that Wordwall not only strengthens academic performance but also nurtures essential soft skills that support holistic student development.